Headache at stroke onset: the Lausanne Stroke Registry. Issue 4 (April 1995) - Kumral, E; Bogousslavsky, J; Van Melle, G; Regli, F; Pierre, P
Abstract : Within 12 hours of stroke onset 2506 patients with first ever stroke admitted to the Lausanne Stroke Registry were questioned about headache. Eighteen per cent of the patients reported headache, 14% with anterior circulation stroke and 29% with posterior circulation stroke (p < 0.001). Headache was reported by 16% of the patients with infarct and 36% of those with haemorrhage (p < 0.001). The prevalence of headache was 9% with lacunar infarct, 15% with middle cerebral artery territory infarct, 37% with infratentorial haemorrhage, and 36% with supratentorial haemorrhage. The most common topography of pain was frontal (41%), followed by diffuse headache (27%; p < 0.001). Diffuse (41%) or occipital (30%) headache was particularly frequent with posterior circulation stroke, whereas frontal headache was associated with anterior circulation stroke (51%; p < 0.001). Headache in stroke may be explained in part by involvement of blood vessels (acute distention or distortion) and mechanical (stretch of haemorrhage) stimulation of intracranial nociceptive afferents. Stroke due to dissection was strongly associated with headache (p < 0.001), whereas embolic (cardiac, artery to artery) stroke was more common without headache (p < 0.001), emphasising the role of extracranial v intracranial arteries in the genesis of headache at stroke onset. Moreover, dual trigeminal-vascular and cervical-vascular system involvement in causing headache may explain the lack of correspondence with the "rules of referral" in up to 38% of the cases.